The Role of Physical Activity in Asthma Outcomes: A Review of Recent Studies - Jakub Mikszta; Natalia Mikszta; Tomasz Lorenc; Maciej Michalik; Mateusz Muras; Krzysztof Marcinkowski; Julia Marcinkowska (Quality in Sport)
Purpose of Research